Semiconductor Geopolitics and Strategic Competition: China’s Responses to the CHIPS and Science Act in the Global Political Economy - Ridha Amalia; Mirah Satria Alamsyah; Syuryansyah Syuryansyah; Bagaskara Sagita Wijaya (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2026)
The U.S. CHIPS and Science Act, enacted in 2022, represents a pivotal intervention in global semiconductor politics, designed to reshape the distribution of technological capabilities and constrain China's strategic trajectory. While existing studies have examined this rivalry primarily through the lenses of industrial policy or bilateral trade competition, few have analysed China's responses as deliberate attempts to contest structural power within the global political economy. This article addresses two questions: What are China's strategic responses to the CHIPS and Science Act, and what are the broader implications for the global political economy? Drawing on an integrated framework that synthesizes Robert Gilpin's International Political Economy approach and Susan Strange's concept of structural power, the study employs qualitative case study methodology. Gilpin explains why states treat semiconductor access as a matter of strategic priority, while Strange's four structures, namely security, production, finance, and knowledge, explain how power is exercised through the frameworks governing technological exchange and governance. Findings reveal that China has mobilized state-backed semiconductor funding, expanded research and development capacity, imposed critical mineral export restrictions, deepened BRICS partnerships, and extended the Digital Silk Road, accelerating supply chain disruption, technology standard fragmentation, and the formation of competing technological blocs. The article contributes to the literature by integrating Gilpin's concept of relative gains with Strange's notion of structural power to explain China's responses to the CHIPS and Science Act and their implications for the global political economy.